THE DEVELOPMENT OF MATHEMATIC LEARNING MODULE BASED ON PROJECT BASED LEARNING USING AUGMENTED REALITY TO IMPROVE THE CONCEPTUAL UNDERSTANDING ABILITY - Ariqah, Lulu Luqyana; Armanto, Dian (Smart Education, 2026)
Abstract: This study aims to produce a valid, practical, and effective Mathematics Learning Module Based on Project-Based Learning Using Augmented Reality to Improve Conceptual Understanding Ability, specifically for the topic of Quadratic Equations and Functions. The research employs a development research approach with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study are 34 students from class X-12 at MAN 1 Medan. The object of this study is the Mathematics Learning Module Based on Project-Based Learning Using Augmented Reality. The instruments used include material and media validation questionnaires, teacher and student response questionnaires, and tests to assess students' mathematical conceptual understanding abilities. The results of the study indicate that: (1) The validity of the learning module, based on expert assessments of material and media, received scores of 87.41% and 82.97% respectively, categorized as very valid; (2) The practicality of the learning module, based on teacher assessments, was 93%, categorized as Very Practical, while the practicality score based on student assessments was 81%, also categorized as Very Practical; (3) The effectiveness of the learning module, measured by the classical student learning completion rate, was 97%, with an average conceptual understanding ability score of 92.65%, and the learning time used did not exceed that of normal lessons; (4) The improvement in students' Mathematical Conceptual Understanding Ability after learning using the developed Learning Module showed a significant progress, with an n-gain value in the High category, averaging 0.7.Based on the results of this study, the Module Based can be considered and categorized as valid, practical, and effective. The learning module can serve as an alternative for teachers in their teaching activities and as a guide for other researchers in developing learning modules that align with the characteristics of the application of Project-based Learning. Keywords: Mathematics Learning Module, Project-Based Learning, Augmented Reality, Mathematical Conceptual Understanding, Quadratic Equations and Functions.